PENGARUH GLOBALISASI TERHADAP EKSISTENSI KEBUDAYAAN DAERAH - Saroni, Saroni (Jurnal Ilmiah Kedirgantaraan, 2018)
Development of technology and culture in the modern era, causes the changes of values in the nation, one is the traditional culture. One of the issue according to this fenomena is the degradation of understanding new gereration to the traditional art which is already estaveted by senior generation in Indonesia.Most of the young generation prefer to influenced by other culture and civilization which are more trending and universal according to them.Globalization influences indirectly to the development of Indonesian culture, both negative and positive influence..One of the positive influence is that the young generations now are literate in foreign language, science and technology also in study and communications. That is why they have the opportunity to gain succesful in their life.The competitions in globalization era make every specialis should literate in computer and automation application to gain the succesful in their field.